The Men's Safer Sex (MenSS) trial: protocol for a pilot randomised controlled trial of an interactive digital intervention to increase condom use in men. Issue 2 (16th February 2015) - Bailey, Julia V; Webster, Rosie; Hunter, Rachael; Freemantle, Nick; Rait, Greta; Michie, Susan; Estcourt, Claudia; Anderson, Jane; Gerressu, Makeda; Stephenson, Judith; Ang, Chee Siang; Hart, Graham; et al.
Abstract : Introduction: Sexually transmitted infections (STI) are a major public health problem. Condoms provide effective protection but there are many barriers to use. Face-to-face health promotion interventions are resource-intensive and show mixed results. Interactive digital interventions may provide a suitable alternative, allowing private access to personally tailored behaviour change support. We have developed an interactive digital intervention (the Men's Safer Sex (MenSS) website) which aims to increase condom use in men. We describe the protocol for a pilot trial to assess the feasibility of a full-scale randomised controlled trial of the MenSS website in addition to usual sexual health clinical care. Methods and analysis: Participants: Men aged 16 or over who report female sexual partners and recent unprotected sex or suspected acute STI. Participants (N=166) will be enrolled using a tablet computer in clinic waiting rooms. All trial procedures will be online, that is, eligibility checks; study consent; trial registration; automated random allocation; and data submission. At baseline and at 3, 6 and 12 months, an online questionnaire will assess condom use, self-reported STI diagnoses, and mediators of condom use (eg, knowledge, intention). Reminders will be by email and mobile phone. The primary outcome is condom use, measured at 3 months. STI rates will be recorded from sexual health clinic medical records at 12 months. The feasibility of a cost-effectiveness analysis will be assessed, to calculate incremental cost per STI prevented (Chlamydia or Gonorrhoea), from the NHS perspective. Ethics and dissemination: Ethical approval: City and East NHS Research Ethics Committee (reference number 13 LO 1801). Findings will be made available through publication in peer-reviewed journals, and to participants and members of the public via Twitter and from the University College London eHealth Unit website. Raw data will be made available on request. Trial registration number: Current Controlled Trials. ISRCTN18649610 . Registered 15 October 2013 http://www.controlled-trials.com/ISRCTN18649610 .